Analysis of Hierarchical and Time-phased Model of Large-scale Power Grid Based on Fp-growth Algorithm. (October 2018) - Wang, Tianyue; Hou, Jinxiu; Yu, Zhihong
Abstract: The scale of UHV AC/DC hybrid power grids in China is continuously expanding, and the operational characteristics of power grids have undergone profound changes. With the advancement of measurement technology and communication technology, power data has grown rapidly. Therefore, data mining technology is required to provide safety warnings and risk prevention, and intelligently adjust control strategies to help dispatchers correct the operating status of the power grid. This paper adopts association rules analysis based on fp-growth to construct a hierarchical and time-phased analysis model of power grid, giving association rules for different security and stability levels of the power grid at different time phases. Based on actual historical data of the large-scale power grid and the application of hierarchical and time-phased analysis mode, the association rules of overload conditions of different time periods are extracted.